The Feasibility of Using Renewable Energy on the Current and Future Libyan State Budget (Al-Farooq Journal of Sciences, 2026)
This study aims to present the impaactof the use of clean energy sources on the state   budgeting and on the electricity company and also on the individual through the use of the comparative inductive approach, and the study has ended with several results, including: The use of clean energy in electricity production has an impact on the state budget and also on the financial statements The Electricity Company, in addition to the direct impact on the environment, as well as the continued decline in the cost of electricity production for renewable energy plants creates an opportunity for investment that is offset by the increase in the price of fossil fuel stations, which is reflected in the continuous improvement of the market competitiveness of clean energy technology.The researcher recommended that the Libyan energy strategy should be based on a mix between energy as fossil fuels are integrated with renewable energy sources, as well as laws and legislation to help in this to raise the capacity of renewable energy in Libya to a level comparable to neighboring and global countries
Keywords: Electricity Company, Fossil Fuel, Renewable Energy